Environmental and economic implications of food safety interventions: Life cycle and operating cost assessment of antimicrobial systems in U.S. beef packing industry. (10th October 2018) - Li, Shaobin; Kinser, Courtney; Ziara, Rami M.M.; Dvorak, Bruce; Subbiah, Jeyamkondan
Abstract: Antimicrobial systems in the U.S. beef packing industry are key treatments to improve the microbiological safety of beef products. However, product loss due to discoloration and use of chemicals, energy, and water have environmental and cost implications. This study compared environmental life cycle impacts and relative operating costs among three scenarios of antimicrobial systems currently applied in the commercial U.S. beef packing industry. Key differences between the three scenarios are the dominant use of antimicrobial chemicals, steam, and hot water pasteurization. Findings reveal that antimicrobial systems featured with chemicals result in greater human toxicity, ecotoxicity, and eutrophication impacts while antimicrobial systems featured with steam or hot water pasteurization lead to higher global warming and energy depletion. Contributions within each antimicrobial system were evaluated by: 1) seven components and 2) four intervention steps. Results show that antimicrobial chemical, wastewater treatment, and natural gas use are the three leading contributors across all environmental impacts. Evaluating environmental impact contributions of intervention steps helps target reduction goals in primary intervention steps and reveals potential opportunities for further impact reductions. A relative operating cost analysis of each scenario found revenue loss from discolored products in antimicrobial systems applying thermal pasteurization is the most significant contributor, resulting in higher operating costs than that of antimicrobial system featured with chemicals. This study provides a systematic assessment regarding environmental and cost impacts of three scenarios of antimicrobial systems. Also it can help guide process optimization, and provide a baseline for comparison with future new antimicrobial systems. Graphical abstract: Image 1 Highlights: Environment and cost implications of three antimicrobial systems were evaluated. Chemicals, natural gas, and wastewater dominate all environmental impact indicators. Chemical use contributes mostly to ecotoxicity, eutrophication, and human health impacts. Thermal pasteurization leads to majority of global warming and energy depletion. Antimicrobial systems with thermal pasteurization experience costly product loss.